On Semisecond Submodules - Saadi, Zainab; Ahmed, Ghaleb (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
Let be a right module over a ring with identity. The semisecond submodules are studied in this paper. A nonzero submodule of is called semisecond if for each . More information and characterizations about this concept is provided in our work.